2020
DOI: 10.1186/s13027-020-00335-2
|View full text |Cite
|
Sign up to set email alerts
|

Novel biomarkers with promising benefits for diagnosis of cervical neoplasia: a systematic review

Abstract: Background Cervical cancer screening is slowly transitioning from Pappanicolaou cytologic screening to primary Visual Inspection with Acetic Acid (VIA) or HPV testing as an effort to enhance early detection and treatment. However, an effective triage tests needed to decide who among the VIA or HPV positive women should receive further diagnostic evaluation to avoid unnecessary colposcopy referrals is still lacking. Evidence from experimental studies have shown potential usefulness of Squamous C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 79 publications
(163 reference statements)
2
11
0
3
Order By: Relevance
“…While results such as those mentioned above show that CEA is of great significance for the clinical diagnosis of lung cancer, its role in early diagnosis is less convincing as it has poor specificity and its level of increase in the early stage of lung cancer is not obvious. SCC-Ag exists in squamous epithelial cells, participates in the differentiation of the squamous epithelial layer, participates in tumor growth in tumor cells, and is often used in the diagnosis of squamous epithelial cell-origin cancer ( 18 ). While initially used to screen for cervical cancer, later studies found that SCC-Ag levels are also elevated in lung SCC and SCC-Ag is an effective biomarker for that disease.…”
Section: Discussionmentioning
confidence: 99%
“…While results such as those mentioned above show that CEA is of great significance for the clinical diagnosis of lung cancer, its role in early diagnosis is less convincing as it has poor specificity and its level of increase in the early stage of lung cancer is not obvious. SCC-Ag exists in squamous epithelial cells, participates in the differentiation of the squamous epithelial layer, participates in tumor growth in tumor cells, and is often used in the diagnosis of squamous epithelial cell-origin cancer ( 18 ). While initially used to screen for cervical cancer, later studies found that SCC-Ag levels are also elevated in lung SCC and SCC-Ag is an effective biomarker for that disease.…”
Section: Discussionmentioning
confidence: 99%
“…HPV infections can lead to cervical cancer by causing genetic instability, hyperproliferation, and immortalization of the mucosa. Several molecular markers linked to this neoplastic mechanism are informative [161]. Quantitative chromosomal and DNA aneuploidy analysis is a useful method for detecting H-SIL progression [162].…”
Section: Specimen Adequacymentioning
confidence: 99%
“…Of all the gynecologic cancers, cervical cancer (CC) and endometrial cancer (EC) are the most common tumors of the female genital tract in the world, followed by ovarian cancer [1]. In recent years, numerous studies have demonstrated that abnormally expressed tumor markers may be involved in cancer initiation and progression, such as p16INKa/ki-67, E6/E7, PTEN, and ANXA2 [2][3][4][5][6]. Despite large efforts to develop novel biomarkers, cervical and endometrial cancers continue to be a serious health problem among women [7,8].…”
Section: Introductionmentioning
confidence: 99%